SAT0494 Early toll-like receptor 4 blockade impedes the behavioural and histological characteristics observed in a mia-induced animal model of osteoarthritic pain. (15th June 2017) - Garcia, MM; Pascual, D; Quesada, E; Uranga, JA; Goicoechea, C
Abstract : Background: Contribution of Toll-Like Receptor 4 (TLR4) to pain sensitisation has been demonstrated to occur under chronic pain conditions. We previously described an antinociceptive effect of TLR4-A1, a TLR4 inhibitor, in two chronic pain conditions, peripheral neuropathic pain and osteoarthritis (OA). Objectives: The aim of this study was to evaluate TLR4-A1 effect on allodynia and hyperalgesia in OA model, and to evaluate whether this effect is correlated with changes in spinal glial activation. Methods: Wistar rats weighing 200–250g were used. OA was induced by a single intraarticular injection of 2mg of monosodium iodoacetate (MIA) into the right knee joint of anaesthetised rats. TLR4-A1, 10 mgkg -1, was intraperitoneally administered during the first five days post-MIA injection. TLR4-A1 was synthesised by Dr Quesada. Vehicle-treatment (ethanol:saline, 1:9) was used as control. Each group was composed of 6 animals. After three weeks (day 22 post-MIA injection), animals were sacrificed for tissue collection. L3-L5 spinal segments were collected and embedded in paraffin wax. Eventually, samples were immune-stained with anti-GFAP or Iba-1 antibodies. Photomicrographs were recorded to make montages of the entire spinal cord at a final magnification of 20x (n=3 per lumbar section). Total number of GFAP or Iba-1 positive cells were counted separately in laminas I-II, III-IV and V-VI. Results: Intraarticular injection of MIA increased microglial expression (Iba-1 labelling) in the ipsilateral spinal cord compared to the contralateral side, being the difference statistically significant for the superficial (I-II, +72.25%; P<0.01) and deeper (V-VI, +95.31%; P<0.001) laminae of L3 and for the superficial laminae of L4 (+87.5%; P<0.01). In animals treated with TLR4-A1, Iba-1 labelling in the ipsilateral dorsal horn showed a similar pattern to the contralateral dorsal horn. Pre-treatment with TLR4 blocker prevented microglia activation after MIA-injection in L3 and L4 segments. Intraarticular injection of MIA also increased the number of GFAP-positive activated astrocytes in the ipsilateral spinal cord compared to the contralateral side; in this case, statistically significant differences were found for the superficial (I-II; +41.62%; p<0.01) and middle (III-IV; +64.35%, p<0.001) laminae of L3 sections. GFAP in TLR4-A1-treated rats showed a similar pattern for the ipsi- and the contra-lateral sides. That is, TLR4-A1 prevented L3 increased activated astroglia following MIA-injection. Conclusions: Early toll-like receptor 4 blockade hampers spinal glial activation, which correlates with diminished allodynia and hyperalgesia observed in TLR4-A1-treated animals in a model of MIA-induced OA. Although further studies are needed, TLR4 blockade could be a good option in the treatment of osteoarthritis. Acknowledgements: Franco R and Marquez A for technical support. Granted: Ministerio de Economía y Competitividad. SAF2012–40075-C02–01. Disclosure of Interest: None declared